Regional Economies in Action Standardization of Transport Amphorae in the Roman and Byzantine Mediterranean: Proceedings of the International Conference at the Austrian Archaeological Institute and the Danish Institute at Athens, 16-18 October 2017 - Horacio González Cesteros; Leidwanger, Justin (Holzhausen, 2023)
The volume contains 13 contributions dealing with ancient and medieval economy from an archaeological perspective based on the standardization of material evidences. Standardization has always been a problematic subject for archaeologist dealing with economic studies in pre-industrian periods. In this volume we deal with this subject from the study of the pottery containers that brought liquid commodities from the different Mediterranean regions during the 1st millenium BC until the late Middle Ages.